Managing children's postural risk when using mobile technology at home: Challenges and strategies - Ciccarelli, Marina; Chen, Janice; Vaz, Sharmila; Cordier, Reinie; Falkmer, Torbjorn (Elsevier, 2015)
Maintaining the musculoskeletal health of children using mobile information and communication technologies (ICT) at home presents a challenge. The physical environment influences postures during ICT use and can contribute to musculoskeletal complaints. Few studies have assessed postures of children using ICT in home environments. The present study investigated the Rapid Upper Limb Assessment (RULA) scores determined by 16 novice and 16 experienced raters. Each rater viewed 11 videotaped scenarios of a child using two types of mobile ICT at home. The Grand Scores and Action Levels determined by study participants were compared to those of an ergonomist experienced in postural assessment. All postures assessed were rated with an Action Level of 2 or above; representing a postural risk that required further investigation and/or intervention. The sensitivity of RULA to assess some of the unconventional postures adopted by children in the home is questioned.